The COVID-19 hydroxychloroquine prophylaxis perception of Indian anesthesiologists: A survey-based original article - Shagun B Shah; Akhilesh Pahade; Rajiv Chawla (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: HCQ gained importance following the National Task Force advisory as an anti-SARS-Cov-2 (coronavirus disease-2019 [COVID-19]) drug for frontline healthcare workers (including anesthesiologists). Report of a young anesthesiologist in Assam developing cardiac arrest following HCQ intake for COVID-19 prophylaxis made us even more concerned. A conscious decision has been made by a large majority among us--to have or not to have HCQ. However, less severe complications such as gastrointestinal upset, skin-rash, visual-disturbance, headache, and dizziness even if experienced by HCQ users were likely to go unreported unless shared. The present survey was conducted to assess the prevailing perception among Indian anesthesiologists about HCQ's preventive effect against COVID-19. The information has been pooled together and discussed in this study. Material and Methods: A total of 247 respondents participated in this pan-India survey. The survey questionnaire was prepared using "Google Forms" and conducted via links delivered through WhatsApp and electronic-mail. Results: 55.9% (138/247) of the respondents had consumed HCQ, 38% (94/247) did not, and 6.1% (15/247) were undecided at the time of responding to the survey. In total, 47 respondents who ingested HCQ reported a side-effect, gastritis being the commonest (31). Conclusion: The evidence for the effectiveness of HCQ against COVID-19 in India is reportedly as strong and weak as other drugs that have been promoted. The survey highlights the reasons consumption of HCQ and represents the opinion of 247 practicing Indian anesthesiologists. It informs the benefits and side effects of HCQ, which can help others in reaching a balanced decision.